PEDOFILIA SEBAGAI SEBAB TERJADINYA KEKERASAN SEKSUAL TERHADAP ANAK (Studi Kasus Nomor 46/Pid.Sus/2020/PN Tabanan) - Putri, Sisy Julya; Soekorini, Noenik; Marwiyah, Siti (Peneliti.net, 2024)
The Indonesian Law Number 35 of 2014 regulates the rights and protection of children, recognizing their entitlement to legal protection. Various forms of legal protection are established for almost all legal relationships. Specific provisions in this law address the protection of children against sexual violence offenses. Such protections include prohibiting sexual intercourse with a child using violence or threats, as well as enticing or deceiving a child for sexual activities. Additionally, the law forbids human trafficking and exploitation of children for personal gain. To safeguard the interests of the child victims, the law encompasses measures such as rehabilitation, identity protection through media, safety assurance for witnesses, and access to information regarding case developments.Efforts to protect children from sexual violence require continuous endeavors to ensure their well-being, as children play a significant role in the nation's progress. The level of protection for children should be on par with that of adults since everyone is equal before the law. This calls for a collective responsibility of the state, local governments, communities, and parents in providing safeguarding measures against various forms of abuse perpetrated by irresponsible individuals who exploit children for criminal activities.Child protection efforts can be categorized as direct or indirect, as well as juridical or non-juridical. Direct protection includes supervising, nurturing, and establishing legal regulations to protect children directly. Indirect protection entails prevention and raising awareness about children's rights and responsibilities. These protection efforts may be targeted at children directly or at those surrounding them, such as parents or family members.The Law Number 35 of 2014 explicitly covers protection against violent activities, including sexual violence, political involvement, armed disputes, social riots, and other harmful events. It obliges the government, local authorities, society, and parents to provide protection and ensure the fulfillment of children's rights and best interests. The law aligns with the principles of human rights stated in the 1945 Indonesian Constitution, recognizing children as individuals entitled to grow and develop with adequate protection.